Legal Protection and Rights Fulfilment of People with Mental Health Disorders: An Analysis of Islamic and Health Legal Perspectives - Rohim, Abdal (As-Siyasi: Journal of Constitutional Law, 2024)
This study investigated the protection of rights, equality, and justice for people with mental disorders (ODGJ) from the perspectives of health and Islamic law. This study aimed to determine and analyze the legal protection and fulfilment of health rights for people with mental disorders. This study employed the normative juridical approach and analytical descriptive research. It relied on primary and secondary data collected through library and field research, encompassing primary, secondary, and tertiary legal sources. The collected data were subjected to qualitative and quantitative analyses using a deductive method. These findings indicate that neglected people with mental disorders face barriers to healthcare access, such as a lack of health insurance and the absence of responsible family members. The government must ensure justice in mental health initiatives for neglected people with mental disorders, as they have the same rights as healthy individuals. Social justice should be upheld without discrimination. Islamic teachings emphasize fairness as a universal principle applicable to everyone, including those with mental illnesses. The government must provide legal protection for neglected patients with mental disorders and secure their rights, as outlined in the 45th Constitution (Article 28D, paragraph 1), Mental Health Law (Article 3C), and Human Rights Law. These regulations affirm the entitlement of all citizens to legal protections.